ANALISIS MOTIF ANYAMAN DAN AKTIVITAS FUNDAMENTAL MATEMATIS DALAM SENI MENGANYAM DI DESA PLAOSAN KABUPATEN KEDIRI - Nur Fadilatul Ilmiyah; Annisa Annisa; Azizatul Fitriyah; Berlyana Sukma Vebyanti (Fakultas Tarbiyah Universitas Ibrahimy, 2020)
Mathematical contextualization is interpreted as identifying the existence of mathematics developed by different cultural groups. The existence of ethnomathematics in education offers a learning approach that connects mathematics with the local cultural wisdom of the community. The main focus of this research is to identify ethnomathematics in woven handicrafts in Plaosan Village, Kediri Regency. This research is qualitative descriptive research. Data were collected using observation, documentation, interview, and literature study techniques. The results showed that there were ethnomathematics in woven handicrafts in Plaosan Village. The mathematical elements that can be found in the woven motifs are the concept of the plane, the concept of lines and the relationships between lines, the concept of angles, and the concept of transformational geometry. The fundamental mathematics activities that can be found in the weaving activities are counting, measuring, designing, locating, playing, and explaining.